Essentials of business research methods - Hair, Joseph F.; Babin, Barry; Money, Arthur H.; Samouel, Phillip (New Jersey Wiley & Sons, 2003)
This book covers the essentials of business research for managers. It includes coverage of the increasing role of knowledge management as well as how to conduct information-gathering activities more effectively in a rapidly changing business environment. Because managers increasingly must make decisions based on almost unlimited information in data warehouses, this text provides substantially more coverage of data analysis than other texts.
Includes index
Keywords: Quản trị kinh doanh